STRATEGI BERTAHAN UMKM KOPI ACEH TERHADAP PERSAINGAN PERKEMBANGAN TEKNOLOGI DI ERA DIGITAL: STUDI KASUS KOPI ACEH DI BANDAR LAMPUNG - Pramesta Anggraini, Alina (JMBI (Journal of Marketing and Business Intelligence), 2025)
This study explores the importance of digital promotion and service quality in supporting marketing strategies, especially for targeting the youth market segment. The research focuses on Kopi Aceh, a coffee shop utilizing social media for promotional activities. The objective is to analyze the effectiveness of Kopi Aceh's social media management and identify optimal ways to enhance engagement and event promotion. A qualitative approach using a case study method was applied. Data was collected through direct observation, interviews with the owner and customers, documentation, and literature review. The findings reveal that the management of Kopi Aceh’s social media has been inconsistent and was even inactive for a period, resulting in a decline in promotional reach and customer visits. Further analysis shows that social media plays a significant role in building brand awareness and increasing customer engagement. The study recommends reactivating social media accounts with dedicated management, producing regular content, improving visual appeal, and initiating promotions and collaborations with local communities. These efforts are expected to attract more visitors and expand market reach. In conclusion, consistent digital promotion and improved service quality are crucial to the success of marketing strategies and business sustainability in the current digital era.